Determinants of Low Voter Political Participation in the 2024 Elections in Gunung Sari Ilir Village - Frigita Lestari; Aji Ratna Kusuma; Enos Paselle (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
This study analyzes the determinants of low voter political participation in the 2024 Elections in Gunung Sari Ilir Village by examining three major dimensions: internal psychological and perceptual factors, external socio-economic and environmental barriers, and institutional, administrative, and governance constraints. The research employs a qualitative descriptive approach supported by thematic analysis to identify patterns, interpret respondents' perceptions, and understand the interrelated structure of deterrent variables influencing electoral engagement. The findings indicate that low levels of political efficacy, distrust toward political actors, weak political awareness, and negative political perception interact with socio-economic insecurity, limited information access, mobility constraints, and environmental difficulties that collectively reduce the feasibility and interest of citizens to vote. Meanwhile, systemic issues such as inaccurate voter registry data, low trust in electoral management institutions, administrative complexity, governance failures, and perceived corruption further reinforce disengagement and weaken the legitimacy of electoral processes. These multidimensional conditions suggest that voter participation cannot be understood merely as a matter of individual voluntarism but is influenced by structural forces that require integrated reform strategies across psychological, socio-economic, and institutional domains to rebuild electoral participation capacity